2010
DOI: 10.1186/1471-2164-11-418
|View full text |Cite
|
Sign up to set email alerts
|

Starvation alters the liver transcriptome of the innate immune response in Atlantic salmon (Salmo salar)

Abstract: BackgroundThe immune response is an energy demanding process, which has effects in many physiological pathways in the body including protein and lipid metabolism. During an inflammatory response the liver is required to produce high levels of acute phase response proteins that attempt to neutralise an invading pathogen. Although this has been extensively studied in both mammals and fish, little is known about how high and low energy reserves modulate the response to an infection in fish which are ectothermic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 83 publications
(87 reference statements)
19
85
0
Order By: Relevance
“…A key finding from this study was that LPS-mediated upregulation of cytokines, including IL-1b and IL-8 were observed in both the fed and fasted Arctic charr. This is unlike other animal models where even short term starvation reduces the capacity for immune response activation (Martin et al, 2010). IL-1b is important in initiating inflammatory responses while IL-8 is a potent neutrophil chemotactic factor (Fast et al, 2007) and, together, they act as key mediators of innate immunity.…”
Section: Innate Immune Modulationmentioning
confidence: 78%
See 4 more Smart Citations
“…A key finding from this study was that LPS-mediated upregulation of cytokines, including IL-1b and IL-8 were observed in both the fed and fasted Arctic charr. This is unlike other animal models where even short term starvation reduces the capacity for immune response activation (Martin et al, 2010). IL-1b is important in initiating inflammatory responses while IL-8 is a potent neutrophil chemotactic factor (Fast et al, 2007) and, together, they act as key mediators of innate immunity.…”
Section: Innate Immune Modulationmentioning
confidence: 78%
“…The temporal increase in liver IL-8 levels in the control fed group at 96 h postinjection may be due to the stress of handling and injection (Fast et al, 2007). During an inflammatory response the liver synthesizes high levels of APPs that assists with the neutralization of invading pathogens (Martin et al, 2010). SAA is a positive APP, whose levels have been shown to increase during inflammation (Uhlar and Whitehead, 1999).…”
Section: Innate Immune Modulationmentioning
confidence: 99%
See 3 more Smart Citations